Stability analysis and consistent solitary wave solutions for the reaction-diffusion regularized nonlinear model - İnç, Mustafa; Alqahtani, Rubayyi T.; Iqbal, Muhammad Sajid (Elsevier, 2023)
The reaction-nonlinear diffusion model is analyze analytically, under both logistic and bistable growth regularization. These regularization techniques have been widely apply and employ in models of chemical phase separation. In this study, we mainly focus on construct the different wave structures are with the help of the generalized Riccati equation mapping method. This method is provided us the different hyperbolic, trigonometric, and rational solutions. These solutions help for the dynamic study of the reaction-nonlinear diffusion model. Moreover, for the physical significance, we construct the 3D and their corresponding contour by choosing the different values of the parameters. Additionally for the computational interests of the readers stability and consistency analysis were proved.
Keywords: RND models; Generalize Riccati equation mapping method; Logistic growth; Bistable growth; Analytical wave structures